Study of crystal structure and PL properties of Na21Mg(SO4)10Cl3 :Ce halophosphor - Poddar, Anuradha; Gedam, S C; Dhoble, S J (Recent Research in Science and Technology, 2012)
A new phosphor Na21Mg(SO4)10Cl3 is very interesting for photoluminescence (PL) properties. In this paper we present results concerning the main PL properties of Na21Mg(SO4)10Cl3 activated by Ce at various concentrations. Polycrystalline Na21Mg(SO4)10Cl3: Ce phosphor prepared by wet chemical method have been studied for its PL characteristics showing Ce3+ emission at 341 nm at the excitation of 247 nm due to 5d → 4f transition, This is a good result for the materials which can be used in scintillation applications.